Facilitating social enterprise development through collective marketing: insights from Bukonzo Joint Co-operative Union, Western Uganda. (1st February 2019) - Ikwera, Robert; Twongyirwe, Ronald
Abstract : Collective marketing is an avenue through which farmers could receive higher returns from their produce. Bukonzo Joint Co-operative Union exemplifies this: it has obtained both Fairtrade and organic certifications and, by following the Fairtrade ethos and offering farmers a guaranteed (and often) higher price, potentially has a strong role in livelihood improvement, poverty reduction, social inclusion and rural development. In this study, we showcase the role of collective marketing, explore the challenges and analyse the relevance of finance institutions in the development of co-operatives. Our qualitative study shows that collective marketing mixed with the Fairtrade ethos could strongly encourage social enterprise development and could lead to livelihood improvement in marginalised areas. However, one of the most important barriers is limited finances for the production of high-quality coffee, purchasing members' coffee under the Fairtrade label and investment in infrastructure: availability of ethically appropriate, affordable funding options is critical in the development of social enterprises.